Igra v igri kot intertekstualni in intermedialni pojav - Orel, Barbara (Slavistična revija, 2002)
The article places a play within a play among the explicit (quotational) intertextual phenomena and shows that in modern drama the dialogic structure of the citing work and of the embedded work was used to deconstruct the classic, closed forms of drama founded on Aristotleian principles.
Keywords: drama; dramatika; gledališče; igra v igri; intermedialnost; intertekstualnost; Intertextuality; teatrologija; tekstna lingvistika; theater